SYMPHONY OF GROWTH: EFEKTIVITAS PEMBELAJARAN MUSIK UNTUK MERANGSANG KETERAMPILAN SOSIAL-EMOSIONAL PADA ANAK USIA DINI - Luthfillah, Nuruzahra; Masum Aprily, Nuraly; Hendri Mulyana, Edi; Qonita, Qonita (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2024)
Social-emotional skills are one aspect of development that must be the main focus in development, because from an early age children are required to be able to live socially. The aim of this research is to determine the effectiveness of music learning for developing social emotional skills. This research method uses descriptive qualitative research with a case study type at the UPI Tasikmalaya Laboratory Kindergarten educational institution. Data collection techniques were carried out using primary and secondary data, primary data was obtained from research results and secondary data was obtained from books and journal articles which were referred to as additional data in data analysis. Data processing and analysis is based on the results of interviews with 2 informants including the class teacher and accompanying teacher, observation and documentation. The research results explain that there is a positive impact on applied music learning, such as: expressing feelings, being patient, working together, being responsible, and managing emotions, so that music learning is very effective in developing children's social emotional skills.